Early Serum HBsAg Drop Is a Strong Predictor of HBeAg Seroconversion and HBsAg Loss to Pegylated Interferon Alfa-2a in Chronic Hepatitis B Patients with Prior Nucleos(t)ide Analogue Exposure - Chen, Qing (Med Sci Monit, 2019)
BACKGROUND: High rates of HBeAg and/or HBsAg seroconversion or clearance have been achieved in chronic hepatitis B (CHB) patients receiving pegylated interferon (pegIFN) in addition to ongoing nucleos(t)ide analogue (NUC) treatment. In the present study, we aimed to evaluate HBsAg kinetics to predict HBeAg seroconversion and HBsAg clearance in these patients. MATERIAL/METHODS: A total of 33 HBeAg-positive and 17 HBeAg-negative patients were enrolled between January 2010 and January 2018. At the end of pegIFN treatment, 9 of 50 patients achieved HBsAg clearance, and 9 of 33 HBeAg-positive patients achieved HBeAg seroconversion. RESULTS: The cutoff value of 0.41 log(10) IU/mL in HBsAg decline at week 12 had a positive predictive value (PPV) of 58.3% and a negative predictive value (NPV) of 94.6% for HBsAg clearance. The cutoff value of 1.94 log(10) IU/mL in HBsAg decline at week 24 had a PPV of 80.0% and an NPV of 97.5% for HBsAg clearance. The cutoff value of 0.47 log(10) IU/mL in HBsAg decline at week 12 had a PPV of 83.3% and an NPV of 85.2% for HBeAg seroconversion. The cutoff value of 1.29 log(10) IU/mL in in HBsAg decline at week 24 had a PPV of 85.7% and an NPV of 88.5% for HBeAg seroconversion. CONCLUSIONS: Early HBsAg drop has a high predictive value for HBsAg clearance and HBeAg seroconversion in patients who were treated with combination therapy of pegIFN and NUCs.